Genocide on the Drina River - Bećirević, Edina, 1967- (Yale University Press, 2014)
In this scholarly yet intensely personal history, Edina Bećirević explores the widespread ethnic cleansing that occurred in Bosnia and Herzegovina from 1992 through 1995, war crimes and crimes against humanity committed by Serbs against Bosnian Muslims that fully meet the criteria for genocide established after World War II by the Genocide Convention of 1948.